Conquest - An Open-Source Dialog System for Conferences - Bohus, Dan; Puerto, Sergio Grau; Huggins-Daines, David; Keri, Venkatesh; Krishna, Gopala; Kumar, Rohit; Raux, Antoine; Tomko, Stefanie (Proceedings of HLT-NAACL 2007, Rochester, NY, 2007)
We describe ConQuest, an open-source, reusable spoken dialog system that provides technical program information during conferences. The system uses a transparent, modular and open infrastructure, and aims to enable applied research in spoken language interfaces. The conference domain is a good platform for applied research since it permits periodical redeployments and evaluations with a real user-base. In this paper, we describe the system’s functionality, overall architecture, and we discuss two initial deployments.